The Concept of State Responsibility in Fulfilling the Rights of Persons with Disabilities in the Manpower Sector in Indonesia - Warsono; Mashari (International Journal of Criminology and Sociology, 2021)
This study aims to analyze the implementation of state responsibilities in fulfilling the rights of persons with disabilities in the field of employment in Indonesia and the supporting and inhibiting factors of the state in fulfilling the rights of persons with disabilities in the field of employment. The method used in this research is normative legal research, with legal studies using legal systematics, research that will synchronize regulations, and make comparisons with applicable laws and use legal history. The study results found that the state fulfills the rights of persons with disabilities in the field of employment by providing protection and fulfillment of the rights of persons with disabilities. Supporting factors for social movements in voicing the fulfillment of the rights of persons with disabilities, which are accommodated by the Indonesian Association of Persons with Disabilities, are supporting factors for the fulfillment of facilities for persons with disabilities in public spaces. The inhibiting factor is that the fulfillment of the rights of people with other disabilities is still lacking; it is proven that facilities for people with disabilities often make the facilities that have been built at several points ineffective and ineffective. The concept of state responsibility in fulfilling the rights of persons with disabilities in the field of employment in Indonesia to obtain work and a decent living for humanity is a constitutional right guaranteed in the 1945 Constitution of the Republic of Indonesia.